2016
DOI: 10.1128/aem.03573-15
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Inactivation of Enteric Viruses and Bioaccumulation of Enteric Foodborne Viruses in Live Oysters (Crassostrea virginica)

Abstract: f Human enteric viruses are among the main causative agents of shellfish-associated outbreaks. In this study, the kinetics of viral bioaccumulation in live oysters and the heat stabilities of the predominant enteric viruses were determined both in tissue culture and in oyster tissues. A human norovirus (HuNoV) GII.4 strain, HuNoV surrogates (murine norovirus [MNV-1], Tulane virus [TV]), hepatitis A virus (HAV), and human rotavirus (RV) bioaccumulated to high titers within oyster tissues, with different pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 67 publications
3
34
0
Order By: Relevance
“…However, Tian, Yang, Quigley, Chou, and Jiang () and Arthur and Gibson () reported higher D ‐values at 56 °C of 11.8 and 4.03 min, respectively, whereas at 63 °C, reported D ‐values were 2.6 and 1.18 min, respectively, in 1.5 mL microcentrifuge tubes using the first‐order model. Others reported a D ‐value of 2.38 min at 62 °C in cell‐culture media in capillary tube with the first‐order model (Araud et al., ). In this study, a D ‐value of 1.74 min at 56 °C in 2‐mL glass vials was obtained, which appears to be in the lower range of earlier reported values at 56 °C, though somewhat closer and higher than the values reported for 55 °C by Hirneisen and Kniel ().…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Tian, Yang, Quigley, Chou, and Jiang () and Arthur and Gibson () reported higher D ‐values at 56 °C of 11.8 and 4.03 min, respectively, whereas at 63 °C, reported D ‐values were 2.6 and 1.18 min, respectively, in 1.5 mL microcentrifuge tubes using the first‐order model. Others reported a D ‐value of 2.38 min at 62 °C in cell‐culture media in capillary tube with the first‐order model (Araud et al., ). In this study, a D ‐value of 1.74 min at 56 °C in 2‐mL glass vials was obtained, which appears to be in the lower range of earlier reported values at 56 °C, though somewhat closer and higher than the values reported for 55 °C by Hirneisen and Kniel ().…”
Section: Resultsmentioning
confidence: 99%
“…Studies on the heat treatment analysis of the capsid integrity of TV showed that at 80 °C after the shortest time point of 5 s, the appearance of the heated virus changed with the loss of normal round structure, which was accompanied with appearance of rough edges (Araud et al., ). It is known that the protruding domain of the capsid protein is responsible for viral entry into the host cell (Yu et al., ); therefore, the loss of capsid integrity can potentially lead to reduction in host cell binding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, considerably more study of different treatments and additional controls on the internal temperature and its distribution in the food matrix would need to be conducted to confirm this. In another study in oysters, a similar phenomenon of a protective effect of oyster matrices against heat treatment of MNV and TV was observed (Araud et al, 2016), but as with the strawberry puree, the mechanism of the protective effect was beyond the scope of the study. One potential mechanism of a protective effect could be viral binding to carbohydrates present in the strawberry and oyster matrices, as such binding has been shown to protect the virus in the case of binding to bacterial cell surface carbohydrates .…”
Section: Thermal Inactivationmentioning
confidence: 57%
“…Several post-harvest techniques have been proposed to reduce HuNoV in live oysters including cold and high temperature, UV treatment, and high-hydrostatic pressure. However, most of these treatments have low log reduction on norovirus or they kill oysters (Araud et al, 2016, Ye et al, 2015Venugopal, 2005).…”
Section: Introductionmentioning
confidence: 99%